PENGELOLAAN NILAI INTI KARAKTER ENTREPRENEURSHIP DALAM PEMBELAJARAN MATEMATIKA (Studi Fenomenologi di SMP Lazuardi Kamila GIS Surakarta) - Ihwan, Lutfi Patria; , Prof. Dr. Sutama, M.Pd (2015)
This article describes how entrepreneurship character being managed in mathematics education through the management of passion about learning, self-esteem, optimism, and interpersonal communication skill. In this article, the authors using qualitative research design with phenomenology perspective. Data collection has been done in SMP Lazuardi Kamila GIS Surakarta with observation, interview, and documentation methods. The informant were students, teachers, and the principal. Data analysis using interactive models. Data validation using data triangulation. The findings of this article were the managing of passion about learning were shown with the managing of students interest, flow in activity, and mastery orientation. The authors attempted to interpret the findings which known that passion about learning management could impact on students motivation and emotion which affect on student achievement. Self-esteem management were shown with respond to the math fear and anxiety, focus on students positive, and supportive condition. The authors attempted to interpret the findings which known that self-esteem management could impact on students motivation and performances with students will do more effort in the future. Optimism management were shown with teacher doing encouragement, build up the child, lead feeling of "I can", focus on students effort and ability, and notice improvement. The authors attempted to interpret the findings which known that optimism management could impact on how students feel that "they can" so the students have risk taking behaviour, ability thinking problem and will doing better in the future. Interpersonal communication skill management were shown with respect behaviour, teacher paying attention, and having a caring. The authors attempted to interpret the findings which known that interpersonal communication skill management could impact on student ability to learn collaboratively, making sure the student learn important content and skill, and also bolster student self-esteem and self efficacy.